Meta-analysis of in-hospital delay before surgery as a risk factor for complications in patients with acute appendicitis. Issue 8 (14th June 2018) - van Dijk, S T; van Dijk, A H; Dijkgraaf, M G; Boermeester, M A
Abstract: Background: The traditional fear that every case of acute appendicitis will eventually perforate has led to the generally accepted emergency appendicectomy with minimized delay. However, emergency and thereby sometimes night-time surgery is associated with several drawbacks, whereas the consequences of surgery after limited delay are unclear. This systematic review aimed to assess in-hospital delay before surgery as risk factor for complicated appendicitis and postoperative morbidity in patients with acute appendicitis. Methods: PubMed and EMBASE were searched from 1990 to 2016 for studies including patients who underwent appendicectomy for acute appendicitis, reported in two or more predefined time intervals. The primary outcome measure was complicated appendicitis after surgery (perforated or gangrenous appendicitis); other outcomes were postoperative surgical-site infection and morbidity. Adjusted odds ratios (ORs) were pooled using forest plots if possible. Unadjusted data were pooled using generalized linear mixed models. Results: Forty-five studies with 152 314 patients were included. Pooled adjusted ORs revealed no significantly higher risk for complicated appendicitis when appendicectomy was delayed for 7–12 or 13–24 h (OR 1·07, 95 per cent c.i. 0·98 to 1·17, and OR 1·09, 0·95 to 1·24, respectively). Meta-analysis of unadjusted data supported these findings by yielding no increased risk for complicated appendicitis or postoperative complications with a delay of 24–48 h. Conclusion: This meta-analysis demonstrates that delaying appendicectomy for presumed uncomplicated appendicitis for up to 24 h after admission does not appear to be a risk factor for complicated appendicitis, postoperative surgical-site infection or morbidity. Delaying appendicectomy for up to 24 h may be an acceptable alternative for patients with no preoperative signs of complicated appendicitis. Abstract : Delay is safe